(untitled) (Journal of Asian Geography, 2022)
Participatory Irrigation Management (PIM) is a collective action in which water users/farmers and Irrigation Agency (IA) officers work together to ensure better water management. Farmer Organisations (FOs) are autonomous in forming their rules to enhance farmers’ participation in collective action to manage their local commons within an irrigation scheme. However, decreasing the head-tail disparity in water supply, agricultural production, farmer income and farmers’ participation in PIM is still challenging. Walawe, one of the PIM based irrigation schemes in Sri Lanka, is experiencing failures in water management at tail-ends. Therefore, the objectives of this study are to identify the level of tail-end farmers’ participation under existing FO rules while examining the spatial variation of their’ contribution to collective action. 482 irrigation plots’ head farmers of the Bata-atha tail-end branch canal’s command area in the Walawe irrigation scheme was selected for the questionnaire survey using systematic random sampling. Focused Group Discussion (FGD) was conducted to choose collective actions to measure Participation Index (PI). According to the study findings, the range of PI spans from 0 to 11, with a mean of 6.61 and a median of 8. The minimum value of PI is 0, and the maximum value is 11. The highest frequency scores are 9 and 8, obtained by 26.1% and 25.3% of respondents. 11.4% of respondents in the study area scored the lowest value of 0 and 1. The study found that 58.9% of the respondents were actively participating, and 41.1% were inactive in participation when considering the minimum number of times specified for participation. The compliance and contribution of tail-end farmers in PIM were significantly varied along with the head and tail-end of the branch canal and the distributary canals compared to the field canal level. Canal rehabilitation failures, seasonal water supply issues, lack of extension services at the field level, absence of farmer training, and lack of coordination among FOs, IA and farmers at the block level are the identified causes of increased non-participants at tail-ends. This study highlights the needy for capacity building of FOs through focused tail-end farmer group training and extending agricultural extension services through IA.